Enterobacterial Repetitive Intragenic Consensus (ERIC) Genotyping of Escherichia coli O157:H7 - Ooi, Wai Ling; Son, Radu; Gulam, Rusul; Mohamed Ismail, Abdul Karim; Endang, Purwati; Samuel, Lihan (Capricon Publication, 2000)
A total of 30 strains of Escherichia coli O157:H7 isolated from beef and chicken burger were characterized by Enterobacterial Repetitive Intragenic Consensus (ERIC) genotyping. The ERIC polymorphism patterns obtained as illustrated in a dendrogram showed a significant discriminatory fingerprint among the 30 E. coli O157:H7 strains. Nearly every isolates had a unique fingerprint and that there were no bands that were highly conserved among the isolates. This study suggests that there is considerable genetic heterogeneity among the E. coli O157:H7 strains by ERIC PCR, and that this has application in screening strains from clinical or food samples to detect a virulent strain with a known fingerprint, and to trace its dissemination.